Developments in Abrasive Water Jet Machining of Nonmetals - Gupta, Kapil (Politeknik Negeri Jakarta, 2024)
Abrasive water jet machining (AWJM) is known for precise cutting of metals and nonmetals. In the past few years, this machining technology has undergone some important developments which possibly enhanced its capability and extended its applications. This article presents such important developments and related attempts on AWJM made by researchers in the recent past. The scope covers AWJM of important nonmetallic materials like rock, glass, rubber, composites and ceramics etc. The important developments have been in the form of utilizing abrasives like sugar particles, glass beads, ice particles, bone powder; water-less abrasive jet machining; process optimization; and acoustic emission monitoring etc. that enhanced the capability of the AWJM process towards cost reduction, quality enhancement, and sustainability. The article intends to amass such important information related to the recent developments in AWJM for nonmetal cutting and aims to facilitate scholars and researchers with this new knowledge.